2016
DOI: 10.1038/ejcn.2016.157
|View full text |Cite
|
Sign up to set email alerts
|

Why do women stop breast-feeding? Results from a contemporary prospective study in a cohort of Australian women

Abstract: Maternal concerns regarding breast trauma, milk supply and infant satiety were central mediators of breast-feeding duration among these Queensland women. Further research into the antecedents of sucking pathologies and reasons for nipple trauma is indicated. Health professionals can assist women to recognise cues of hunger and satiety in their infants and understand the dynamics and natural history of breast-feeding to prolong breast-feeding relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 36 publications
3
25
0
1
Order By: Relevance
“…Quality assessment was conducted for 21 papers using the appropriate critical appraisal checklist. Following quality assessment, five papers were excluded (Katz, Nilsson, & Rasmussen, ; Lewkowitz et al, ; Newby & Davies, ; Rasmussen, Lee, Ledkovsky, & Kjolhede, ; Zanardo et al, ) due to poor quality of data presented. Quality assessment scores of the final included papers are included in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality assessment was conducted for 21 papers using the appropriate critical appraisal checklist. Following quality assessment, five papers were excluded (Katz, Nilsson, & Rasmussen, ; Lewkowitz et al, ; Newby & Davies, ; Rasmussen, Lee, Ledkovsky, & Kjolhede, ; Zanardo et al, ) due to poor quality of data presented. Quality assessment scores of the final included papers are included in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies (Mok et al, ; Jarlenski et al, ; Kair & Colaizy, ; Massov, ; O'Sullivan et al, ; Claesson et al, ) reported that women who were overweight or obese were more likely to report insufficient breastmilk as a reason for early cessation of breastfeeding than women with normal BMIs. This is one of the most commonly reported reasons for early cessation generally in high‐income country settings, including Australia, UK, and Canada (Brown, Dodds, Legge, Bryanton, & Semenic, ; McAndrew et al, ; Newby & Davies, ) and may be an indicator of other reasons for stopping breastfeeding, as insufficient milk of itself is unlikely if women are breastfeeding effectively. However, the included studies did not fully explore this reason or define what “insufficient breastmilk” actually meant.…”
Section: Discussionmentioning
confidence: 99%
“…22 Insufficient milk may be the justification given because it is a socially acceptable reason for discontinuing breastfeeding or may be a reflection of the negative influences of medicalization and commercialization on women's trust in their own capacity to feed their infants. 24 An Australian study showed that the frequency and duration of breastfeeding sessions naturally diminishes over the first six months due to the increase in the child's efficiency in extracting milk. 24 However, such changes may be interpreted as a "lack of interest" or "insufficient milk".…”
Section: Mothers Who Did Not Breastfeedmentioning
confidence: 99%
“…24 An Australian study showed that the frequency and duration of breastfeeding sessions naturally diminishes over the first six months due to the increase in the child's efficiency in extracting milk. 24 However, such changes may be interpreted as a "lack of interest" or "insufficient milk". If the issue is an erroneous interpretation on the part of the mother, education is essential, as knowledge regarding the course of lactation can contribute to calming mothers with regards to normal variations and avoid the unnecessary use of baby formulas and the premature discontinuation of breastfeeding.…”
Section: Mothers Who Did Not Breastfeedmentioning
confidence: 99%
“…The highest breastfeeding attrition rate occurs in the first month postpartum with exclusive breastfeeding rates as low as 57.1% [9]. The mother's view of the sufficiency of her breast milk supply (perceived insufficient milk-PIM) is a paramount concern for breastfeeding globally [10] [11][12] [13]. International data show that mothers 'read' the adequacy of their infant's crying and fussiness [14] [15], frequent feeding demands [16], and perceived infants' poor weight gain [17] [18] as signs that the mother's milk supply is inadequate.…”
Section: Introductionmentioning
confidence: 99%